V˙O2 kinetics and tethered strength influence the 200-m front crawl stroke kinematics and speed in young male swimmers - Sokołowski, Kamil; Bartolomeu, Raul Filipe; Barbosa, Tiago Manuel; Strzała, Marek (Frontiers in Physiology, 2022)
Background: The aim was to examine the relationship of fast developed in 1-minute 〖V ̇O〗_2 and force indices measured both in tethered swimming test, and to assess the influence of gathered indices on 200-m front crawl race – speed and swimming kinematics. Methods: Forty-eight male swimmers participated in this study (13.5 ± 0.9 years old). Testing included: a) 1-minute all-out front crawl tethered swimming while oxygen consumption (breath-by breath) and tethered forces are measured, b) 200-m front crawl race-like swimming featuring kinematic analysis, and c) biological age (BA) examination. Results: Statistical analysis included BA control. During 1-min all-out tethered swimming test linear increase of oxygen consumption was observed. There were moderate to high partial correlations between particular second periods of 1-minute 〖V ̇O〗_2 – 31-60, 41-60, 51-60 and Fmax, Fave, Iave of tethered swimming. 41-60, 51-60 〖V ̇O〗_2 were moderately to highly interrelated with all the swimming speed indices and SI. Swimming speed indices significantly interplayed with SL, SI, Fmax, Fave, Iave. Conclusions: The ability of fast reaching high 〖V ̇O〗_2 is essential for swimmer’s energy production at short and middle-distance events. Reaching high level of 〖V ̇O〗_2 determined significantly tethered strength and swimming kinematics. Level of 〖V ̇O〗_2 influenced the maintenance of a proper pulling force and stroke technique of front crawl swimming in young male swimmers.